Peran Jenjang Karir Dan Work Life Balance Terhadap Kinerja Karyawan - Salma Tamsyiatissanusiyah; Acep Samsudin; Asep Muhamad Ramdan (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The aims of this study are to find out the career ledder and work life balance and their role on the performance of three-star hotels employees in Sukabumi. This research was conducted on employees of three-star hotels in Sukabumi by distributing questionnaires. The method used in this study was a quantitative method with human resources approach. There were 3 variables used as research areas, namely career ledder, work life balance, and employee performance. The career ledder and work life balance were independent variables, whereas employee performance was the dependent variable. In this study, operational variables regarding the variables studied, concepts, indicators, units of measure, and scale of measurement were used as a reference in making questionnaires. The number of samples of 161 was calculated by the Slovin formula. The data analysis technique used were determinant coefficient and multiple linear regression. The analysis was carried using the SPSS 16 application. Validity, reliability, and normality tests were also done in order to obtain valid, accurate, and normal data. Based on the results of the analysis of operational variables, it is known that the career path variable gets an average score of 4.728, the work life balance variable gets an average score of 4.772, and the employee performance variable gets an average score of 3.727. The results of testing the variable hypothesis showed a number of 84,433, which means that career ledder and work life balance have a significant influence on employee performance. Keywords: Career Ledder, Employee Performance, Human Resources, Work Life Balance.